Telemedicine in non-communicable chronic diseases care during the COVID-19 pandemic: exploring patients' perspectives - Habbash, Fatema; Rabeeah, Aamal; Huwaidi, Zainab; Abuobaidah, Hiba; Alqabbat, Jumana; Hayyan, Fatema; Almarabheh, Amer; Al Sindi, Hind; Ben Salah, Afif (Frontiers in Public Health, 2023)
Purpose: This study aimed to explore challenges facing patients using Telemedicine consultations in non-communicable chronic disease clinics in primary care settings and to evaluate their satisfaction and willingness to use this service in the future. Methods: This is an analytical cross-sectional study enrolling participants who were randomly selected from representative primary care centers in Bahrain and providing Telemedicine consultations. A semi-structured questionnaire permitted data collection using telephone interviews. Results: A total of 251 individuals participated in the study of whom the majority were Bahraini (90.04%), and the mean age was 54.48 ± 10.78 years. Most of the participants 231 (92.03%) were satisfied with the Telemedicine consultation while only 142 (56.80%) were willing to use this service in the future. The main perceived challenges related to Teleconsultations were the lack of physical examination, inadequate time of TM consultation, fear of medical errors, and lack of privacy. The willingness to use TM consultation in the future was mainly determined by the degree of comfort to tell private information (p< 0.01) and to less extent the ease of the communication tool (p = 0.005) on multivariate analysis. Conclusion: TM consultations could be a good complement to conventional consultation formats in the future. The sustainability of this innovative healthcare delivery tool requires addressing acceptability by users, ease of use, patient-centeredness, and technological advances to ensure privacy.